Molecular docking of the interaction of 4,5- phenyl and 4,5- furyl imidazoles with T. Cruci, T. Brucei and L. Infantum Cyp51 enzymes - Castro-Piñol, Mariana; García-López, América; Rojas Vargas, Julio; Acevedo Martínez, Jorge (Revista Cubana de Química, 2022)
The subspecies Leishmania spp., Trypanosoma cruzi and Trypanosoma brucei are the causative agents of leishmaniasis, American trypanosomiasis and human African trypanosomiasis respectively. These diseases are not prioritized on the bigger pharmaceutical companies, since they usually affect the poorest countries and the drugs that are available for their treatment are inefficient, old and toxic. In order to find pharmacological alternatives, the following investigation is carried out, which explores in silico study through molecular docking, the difference of using phenyl or furyl groups in positions 4 and 5 of imidazoles as potential antiprotozoa against Leishmania spp. , Trypanosoma cruzi and Trypanosoma brucei. It seems to be a general rule that phenyl groups achieve a greater decrease in free binding energy, which indicates a greater affinity for the proteins studied, however there are exceptions due to geometric particularities of the active sites and the structures of the imidazoles.